The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24087546
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Hemoglobin Genotypes Affect Malaria Parasite Growth and Correlate with Exosomal miR-451a and let-7i-5p Levels

Abstract: Malaria affects a significant portion of the global population, with 247 million cases in 2021, primarily in Africa. However, certain hemoglobinopathies, such as sickle cell trait (SCT), have been linked to lower mortality rates in malaria patients. Hemoglobin (Hb) mutations, including HbS and HbC, can cause sickle cell disease (SCD) when both alleles are inherited (HbSS and HbSC). In SCT, one allele is inherited and paired with a normal allele (HbAS, HbAC). The high prevalence of these alleles in Africa may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…These EVs contain parasite‐specific bioactive substances including proteins, RNA, lncRNA and nucleic acids. In human protozoan parasitic diseases such as malaria, African sleeping sickness, Chagas disease, leishmaniasis and toxoplasmosis, EVs serve as a carrier of effector molecules that modulate the host immune response to establish infection (da Silva Lira Filho et al., 2021 ; Dias‐Guerreiro et al, 2021 ; Higuchi et al, 2018 ; Li, Xiu, et al, 2018 ; Oxendine Harp et al, 2023 ). It was reported that Leishmania EVs can transfer Leishmania RNA virus 1 (LRV1), a virus that infects Leishmania and enhances its virulence, to macrophages and induce type‐I interferon responses (Atayde et al., 2019 ).…”
Section: Roles Of Evs In the Pathogenesis Of Infectious Diseasesmentioning
confidence: 99%
“…These EVs contain parasite‐specific bioactive substances including proteins, RNA, lncRNA and nucleic acids. In human protozoan parasitic diseases such as malaria, African sleeping sickness, Chagas disease, leishmaniasis and toxoplasmosis, EVs serve as a carrier of effector molecules that modulate the host immune response to establish infection (da Silva Lira Filho et al., 2021 ; Dias‐Guerreiro et al, 2021 ; Higuchi et al, 2018 ; Li, Xiu, et al, 2018 ; Oxendine Harp et al, 2023 ). It was reported that Leishmania EVs can transfer Leishmania RNA virus 1 (LRV1), a virus that infects Leishmania and enhances its virulence, to macrophages and induce type‐I interferon responses (Atayde et al., 2019 ).…”
Section: Roles Of Evs In the Pathogenesis Of Infectious Diseasesmentioning
confidence: 99%